The critical life of Toni Morrison - Mayberry, Susan Neal, 1951- (Camden House, 2021)
"Toni Morrison (1931-2019) is the most important American novelist since William Faulkner, the most significant American woman writer since Emily Dickinson, and the most widely read African American public intellectual of the last half century. Her influence as a writer, critic, editor, teacher, and scholar is profound: she changed the face of literature and literary criticism in the United States, if not worldwide. Yet despite the ever-expanding field of scholarship on Morrison, no monograph tracing the critical reception of her groundbreaking writings has ever been published, an omission the present book corrects. The book is also as much a cultural history of the United States as a reception history of an American writer. Morrison worked brilliantly in many genres-fiction, of course (eleven novels and two published short stories); drama/staged performance; poetry; non-fiction books and essays on historical, social, and political issues; and critical essays on the work of others and on her own work, such as her introductions to other writers' texts, her forewords and afterword to her own novels, and her literary-critical essays like "Home," "Rootedness: The Ancestor as Foundation," and her stunning Nobel Prize Lecture. Playing in the Dark: Whiteness and the Literary Imagination, Morrison's singular effort to generate a literary-critical methodology that recognizes and embraces rather than ignores or remains willfully blind to the African American presence in US literature, transformed American academics' attitude toward American letters. For an African American woman to achieve such literary prominence in the United States is unprecedented (a shameful comment on American racism, as well as sexism) and therefore all the more noteworthy. The story of Morrison's achievement in making a home for herself-and for other women and people of color-in the stony bedrock of "white male" American literature is the subject of this book"-- Provided by publisher.
Keywords: Morrison, Toni -- Criticism and interpretation.; Morrison, Toni; LITERARY CRITICISM / American / General; African American writer.; American literature.; Toni Morrison.; contemporary debates.; cultural integration.; literary criticism.; public intellectual.; Criticism, interpretation, etc.